(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This research examines the role of artificial intelligence (AI) in amplifying the phenomenon of digital disinformation and its implications for security decision-making strategies in the Kingdom of Saudi Arabia. The study begins with the increasing use of generative AI techniques in producing highly realistic and misleading digital content, such as synthetic texts, fake images, deepfake videos, and algorithmically and robotically driven digital campaigns. This makes distinguishing between genuine and fabricated content increasingly difficult. The study’s significance lies in the connection between digital disinformation and national and information security. The dissemination of misleading or distorted information can influence public opinion, disrupt the information environment, and weaken the quality of security decisions if based on inaccurate data. The study focuses on the Saudi context within the framework of the Kingdom’s rapid digital transformation under Vision 2030, and the accompanying increasing reliance on data and modern technologies to support security decision-making. This study aims to analyze the role of artificial intelligence (AI) technologies in producing and disseminating digital disinformation, identifying its most prominent forms and methods, and measuring its impact on the efficiency and effectiveness of security decision-making. It also seeks to assess the readiness of security institutions and decision-makers to confront these threats. Furthermore, the study aims to propose practical mechanisms to mitigate the impact of digital disinformation by enhancing technological awareness, developing early detection tools, and employing counter-AI technologies within the national security framework.